Development of Hybrid Thermoelectric and Photovoltaic Power Generation - M. S., Jadin; Nur Asyikin, Setapa; Amir Izzani, Mohamed (2015)
Hybrid photovoltaic and thermoelectric systems more effectively convert solar energy into electrical energy. Two sources of energy are used in this project. One of the energy is solar energy that converts radiant light to electrical energy. The other one is heat energy, which converts heat energy into electrical energy. Therefore, this project will utilize both of the solar radiation and heat from the sun as to generate more electricity. The aim of this project is to build a hybrid system that will increase the efficiency of the power generation system. In this research, the output power of the hybrid is equal to the sum of the maximum output power that produced separately from the individuals of the PV module and TE generator devices. The maximum output power that can be generated was up to 99.27 watts respectively. Overall, by using hybrid PV-TE generator system, the output that can be generated is better than the individual system.